2018
DOI: 10.18632/aging.101685
|View full text |Cite
|
Sign up to set email alerts
|

Integrated multi-omics characterization reveals a distinctive metabolic signature and the role of NDUFA4L2 in promoting angiogenesis, chemoresistance, and mitochondrial dysfunction in clear cell renal cell carcinoma

Abstract: An altered metabolism is involved in the development of clear cell - renal cell carcinoma (ccRCC), and in this tumor many altered genes play a fundamental role in controlling cell metabolic activities. We delineated a large-scale metabolomic profile of human ccRCC, and integrated it with transcriptomic data to connect the variations in cancer metabolism with gene expression changes. Moreover, to better analyze the specific contribution of metabolic gene alterations potentially associated with tumorigenesis and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
115
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(130 citation statements)
references
References 29 publications
3
115
0
Order By: Relevance
“…25,27 Moreover, ccRCC is a metabolic disease, characterized by metabolic reprogramming. 28,29 The metabolic flux through glycolysis is partitioned and mitochondrial bioenergetics and oxidative phosphorylation are impaired in ccRCC, as well as lipid metabolism, 30 as supported by the results of GO and KEGG analyses in this study, which indicated a role for CLDN8 in oxidative phosphorylation. GSEA analyses showed enrichment in several tumor-related pathways.…”
Section: Discussionsupporting
confidence: 81%
“…25,27 Moreover, ccRCC is a metabolic disease, characterized by metabolic reprogramming. 28,29 The metabolic flux through glycolysis is partitioned and mitochondrial bioenergetics and oxidative phosphorylation are impaired in ccRCC, as well as lipid metabolism, 30 as supported by the results of GO and KEGG analyses in this study, which indicated a role for CLDN8 in oxidative phosphorylation. GSEA analyses showed enrichment in several tumor-related pathways.…”
Section: Discussionsupporting
confidence: 81%
“…The underlying biopathological changes associated with specific radiomic feature profiles of renal tumor subtypes are not fully understood yet. Some authors hypothesized that radiomic features correlate with the degree of microvessel density [ 22 ] and changes in renal cell metabolism [ 23 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite its increasing incidence in the past two decades, the mortality of ccRCC patients has not decreased (3,18,19). Metabolic alterations are considered a central feature of ccRCC (20) with the reporting of potential interactions of ccRCC with various metabolic reprogramming components (21,22). Additionally, several studies have examined the role of metabolic genes in the RCC processes.…”
Section: Discussionmentioning
confidence: 99%